2013 IEEE Virtual Reality (VR) 2013
DOI: 10.1109/vr.2013.6549357
|View full text |Cite
|
Sign up to set email alerts
|

Burnar: Involuntary heat sensations in augmented reality

Abstract: a) (b) Figure 1: (a) Our BurnAR demonstration enables users wearing a stereo head-worn display to experience the illusion of seeing their own hands burning, which we achieve by overlaying virtual flames and smoke on their hands. (b) Hand movement affects flames and smoke. ABSTRACTAugmented Reality systems that run interactively and in real time, using high quality graphical displays and sensational cues, can create the illusion of virtual objects appearing to be real. This paper presents the design, implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Several AR/VR studies [13]- [16] have shown the possibility of changing user perception by leveraging VFX as visual stimuli. Weir et al [17] and Erickson et al [18] presented that hot or cold VFX could influence the sense of the body temperature. They attached dynamic flames and icy fog on the user's hands or on the surrounding real environment to show them.…”
Section: B Visual Effects Alter Our Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several AR/VR studies [13]- [16] have shown the possibility of changing user perception by leveraging VFX as visual stimuli. Weir et al [17] and Erickson et al [18] presented that hot or cold VFX could influence the sense of the body temperature. They attached dynamic flames and icy fog on the user's hands or on the surrounding real environment to show them.…”
Section: B Visual Effects Alter Our Perceptionmentioning
confidence: 99%
“…For each condition, VHs asked participants to do the survey, which was Visual effects taxonomy to be used in our experiment. We reviewed the previous AR/VR researches [4], [13], [14], [17], [18], [27]- [42] and classified color (Low, High) and form (Exaggerated, Diminished) as 2 × 2 matrices with respect to VFX's visibility.…”
Section: B Materials 1) Physical Setupmentioning
confidence: 99%
“…It is well known in psychology that visual stimuli, the most dominating human sensing modality, can be manipulated to change one's perception of the world [29,30]. Several studies [31][32][33][34] have applied high-visibility visual effects (VFX) augmentation, based on the visual dominance [30], to influence human perception. For example, Weir et al [31] augmented flame effects on the participants' hands, and despite the awareness that flame effects were not real, participants felt warm.…”
Section: Visual Stimuli Altering Our Perceptionmentioning
confidence: 99%
“…Several studies [31][32][33][34] have applied high-visibility visual effects (VFX) augmentation, based on the visual dominance [30], to influence human perception. For example, Weir et al [31] augmented flame effects on the participants' hands, and despite the awareness that flame effects were not real, participants felt warm. Punpongsanon et al [35] manipulated softness perception by altering the appearances of objects when touching them.…”
Section: Visual Stimuli Altering Our Perceptionmentioning
confidence: 99%
“…More recently, Brogni, Caldwell, and Slater () described an experience of illusory touch in which some participants were able to experience sharpness when they touched sharp objects, but not when they touched smooth ones. Using Augmented Reality, Weir and colleagues () reported an illusion in which some participants experienced a sensation of heating after seeing virtual flames overlaid on their hands. These findings have been suggested as a form of virtual synesthesia , which is characterized by a temporary experience of a sensation (either touch, smell, taste, or sound) that results from stimulating a different sense (most commonly vision) during immersion in a virtual environment (Rogowska, ).…”
mentioning
confidence: 99%